Vulnerability Analysis and Ways to Strenghten the Resilience of the Roma Community in Pomurje – A Case Study of Lendava - Lobnikar, Branko; Hojnik Kelenc, Rahela; Prislan Mihelič, Kaja (10. Nacionalna konferenca o varnosti v lokalnih skupnostih: Mirna, varna in inkluzivna družba ter varnost v lokalnih skupnostih, 2024)
The contribution analyses activities related to the Roma community in the local environment, which are not conducted by state institutions but rather by institutions whose primary aim is to strengthen various competencies Roma needs for a better quality of life and work. The analysis consists of two parts: a presentation of the Lendava People's University activities and two interviews with experts on Roma issues – both interviewees were Roma women. The contribution presents the challenges faced by members of the Roma community in Lendava while also demonstrating how local institutions can contribute to their empowerment, which can (potentially) result in fewer issues typically addressed by the police, social work centres, or educational institutions. In addition to the classic vulnerabilities associated with the Roma community (unemployment, segregated housing, discrimination), the contribution highlights less frequently discussed but equally important vulnerabilities related to social isolation and culturally conditioned limitations.